2021
DOI: 10.1002/biof.1764
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin alleviates hepatic fibrosis through inducing ferroptosis in hepatic stellate cells

Abstract: Targeting the elimination of activated hepatic stellate cells (HSCs) and blocking excessive deposition of extracellular matrix are recognized as an effective strategy for the treatment of hepatic fibrosis. As a newly discovered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
(135 reference statements)
1
32
0
Order By: Relevance
“…Previous researches have confirmed that DHA can also result in iron homeostasis imbalance in cancer cells, which in turn leads to ferroptosis [ 18 ]. In addition, previous studies by our team have confirmed that DHA can induce ferroptosis of hepatic stellate cells and reverse the development of hepatic fibrosis [ 19 ]. Here, we will discuss whether DHA can induce HCC ferroptosis and exert an antitumor effect by regulating the formation of the PEBP1/15-LO complex.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Previous researches have confirmed that DHA can also result in iron homeostasis imbalance in cancer cells, which in turn leads to ferroptosis [ 18 ]. In addition, previous studies by our team have confirmed that DHA can induce ferroptosis of hepatic stellate cells and reverse the development of hepatic fibrosis [ 19 ]. Here, we will discuss whether DHA can induce HCC ferroptosis and exert an antitumor effect by regulating the formation of the PEBP1/15-LO complex.…”
Section: Introductionmentioning
confidence: 72%
“…Studies have shown that artemisinin and its derivatives can effectively induce tumor cell ferroptosis [ 24 , 25 ]. In addition, DHA was recently shown to induce ferroptosis in hepatic stellate cells [ 19 ]. Therefore, we hypothesized that DHA exerted antitumor activity in this study mainly by regulating HCC ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of STAT3 signaling was also shown to promote fibrosis in pulmonary, cardiac, and liver disease ( 64 66 ). Research indicated that DHA can prevent fibrogenesis by inhibiting the activation of STAT3 in in vitro and in vivo models of liver fibrosis, skin fibrosis, systemic sclerosis, and pulmonary vascular remodeling, among others ( 67 69 ). Our study provides also first-time evidence that DHA restrains GO-related fibrosis by inhibiting the phosphorylation of STAT3 in OFs.…”
Section: Discussionmentioning
confidence: 99%